(untitled) (Eurasian Journal of Philology Science and Education, 2015)
In the article the process of borrowings of foreign-language words and international terms in the names of modern professions in Kazakhstan is considered. It is known that the main reasons for the use of foreign language vocabulary is the lack of appropriate concepts and modern names in the information base of language-receptor, which leads to borrowing foreign words and terms. Now much attention in research of loans is paid to English and the American lingua-cultural influence as about 3/4 of all borrowings are anglicisms and ameriсanisms. Modern vacancies in Kazakhstan and especially professions in the service sector are exposed to foreign-language expansion that, naturally, complicates understanding of the content and functional features of these or those professions. All names of professions are given in a foreign language and most of all this use of anglicisms.